Measuring. Monitoring. Management. Control - B.V. Chuvykin; I.A. Dolgova; G.V. Milovzorov (Измерение, мониторинг, управление, контроль)
Background. The relevance of the topic is determined by the increasing use of special-purpose sensor-converting equipment in information and measuring systems. The paper raises the problem of restoring pulsed information signals with amplitude distorted due to the limitation of the dynamic range. Materials and methods. To solve the problem, the methods of the mathematical apparatus of the theory of integer functions of exponential type, the theory of wavelets or mathematical models in the time domain were used. When applying these methods, the restoration of the distorted amplitude of pulsed information signals depending on the frequency-time properties of the signals is carried out at the stage of digital processing of the measuring signal by solving systems of linear equations. Results. Necessary and sufficient conditions for recovery of extreme values of amplitudes of pulse signals are considered, using measuring information of undistorted part of signal and a priori information on its frequency-time properties. Examples of recovery algorithms for three classes of measuring pulse signals are given. Conclusions. Analysis of the results of the conducted studies allows us to consider the use of the considered methods in information and measuring systems for solving problems of reducing amplitude distortions caused by a limited dynamic dipason.